2015
DOI: 10.1021/es503848s
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Preferentially Accumulates in the Eye Lens Following Embryonic Exposure: A Confocal X-ray Fluorescence Imaging Study

Abstract: Maternal transfer of elevated selenium (Se) to offspring is an important route of Se exposure for fish in the natural environment. However, there is a lack of information on the tissue specific spatial distribution and speciation of Se in the early developmental stages of fish, which provide important information about Se toxicokinetics. The effect of maternal transfer of Se was studied by feeding adult zebrafish a Se-elevated or a control diet followed by collection of larvae from both groups. Novel confocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…Figure 5 shows a section taken through the eye and brain of a zebrafish larva treated with 2 μM HgCl 2 . In this case the eye lens contains large quantities of selenium, which we have previously observed using confocal methods in selenium supplemented fish, 19 but with the rest of the section showing selenium levels that are more typical of those observed in the trunk section. In particular, pigmented areas of the retina show high relative selenium levels, consistent with those observed in the pigmented areas of the trunk section.…”
Section: Page 2 Of 8 Metallomicssupporting
confidence: 55%
“…Figure 5 shows a section taken through the eye and brain of a zebrafish larva treated with 2 μM HgCl 2 . In this case the eye lens contains large quantities of selenium, which we have previously observed using confocal methods in selenium supplemented fish, 19 but with the rest of the section showing selenium levels that are more typical of those observed in the trunk section. In particular, pigmented areas of the retina show high relative selenium levels, consistent with those observed in the pigmented areas of the trunk section.…”
Section: Page 2 Of 8 Metallomicssupporting
confidence: 55%
“…The function of selenoproteins and the antioxidant properties of excess Se in postnatal mammalian ocular physiology are known to cause oxidative damage via redox cycling and result in cataracts (Flohe, 2005). In situ hybridization (ISH) has been used to localize specific selenoprotein expression in retina of developing zebrafish (Thisse et al, 2003), and confocal X-ray fluorescence imaging of zebrafish offspring of dietary SeMet exposed mothers showed accumulation of Se in the eyes of hatchlings (Choudhury et al, 2015). The highest concentrations appeared in the lens-core followed by the lens-epithelium, and these investigators regarded sulfur-substitution as the mechanism in lens proteins, as opposed to the oft-studied oxidative stress mechanism, and suggested that the eye may be an ideal site to test mechanisms of toxicity (Choudhury et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization (ISH) has been used to localize specific selenoprotein expression in retina of developing zebrafish (Thisse et al, 2003), and confocal X-ray fluorescence imaging of zebrafish offspring of dietary SeMet exposed mothers showed accumulation of Se in the eyes of hatchlings (Choudhury et al, 2015). The highest concentrations appeared in the lens-core followed by the lens-epithelium, and these investigators regarded sulfur-substitution as the mechanism in lens proteins, as opposed to the oft-studied oxidative stress mechanism, and suggested that the eye may be an ideal site to test mechanisms of toxicity (Choudhury et al, 2015). Taken together, even minor ocular impairments in fish could be expected to have direct effects on behavior and survival including visual attraction to food, migration within the water column, and detection of predators (Guthrie, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…CXMFI provides compositional and structural information from precise locations on the surface of, and within, intact particles, with greater spatial precision than can be obtained using conventional micro x-ray fluorescence (µ-XRF) methods [18]. Limited applications of CXMFI are reported for natural materials; examples include the characterization of Se accumulation in fish eye lens [19]; W, Pt, and Fe in particles embedded in a mineralogical matrix [20]; K, Ca, and Fe in rice grains [21]; and U-Th-Pb for dating of geological materials [22].…”
Section: Introductionmentioning
confidence: 99%